The Heterogenous Presentation of Hepatic Mucormycosis in Adults: A Case Report and Review of the Literature - Hazim Allos; Rachel S. Hicklen; Takahiro Matsuo; Javier Adachi; Sebastian Wurster; Dimitrios P. Kontoyiannis (Journal of Fungi)
Hepatic mucormycosis is a rare but often fatal opportunistic fungal infection, primarily affecting immunocompromised patients. Herein, we report such a case from MD Anderson Cancer Center (Houston, TX, USA) and systematically review published cases in patients ≥ 19 years of age to better characterize clinical presentation, diagnostic challenges, and treatment outcomes of hepatic mucormycosis. Among the 40 identified cases (including ours), hematologic malignancies (55%) and solid organ transplantation (30%) were the most common underlying conditions. Fever (70%) and abdominal pain (63%) were the predominant symptoms. Imaging revealed multiple hepatic lesions in 72% of cases. Diagnosis was primarily based on histopathology (73%), whereas culture positivity was low (36%), underscoring the difficulty of pathogen isolation. Mucorales-active antifungal therapy was often delayed but eventually used in 85% of cases (all amphotericin B +/− Mucorales-active triazoles), while 45% underwent additional surgical intervention. Despite treatment, 1-year all-cause mortality remained high at 46%, with a trend towards lower mortality for those who underwent surgery compared to non-surgical management (35% vs. 55%, p = 0.334). These findings highlight the aggressive nature of hepatic mucormycosis and the importance of early recognition as well as the need for non-culture-based diagnostics and multimodal treatment approaches. Improved awareness and further research into optimized management strategies are crucial to improve the outcomes of this challenging infection.